Bioactive compounds from Mesua ferrea stems - Sukanya Keawsa-Ard (2018)
© 2015 Chiang Mai University. All rights reserved. The chemical constituents and biological activities of Mesua ferrea Linn. were studied. The stems of M. ferrea were extracted with hexane, dichloromethane and methanol, respectively. The methanol extract exhibited the highest antibacterial activity against Escherichia coli with the MIC value of 31.25 μg/mL. The methanol extract and the dichloromethane extract exhibited the highest activity against Staphylococcus aureus with the MIC values of 31.25 μg/mL. The dichloromethane extract exhibited anticancer activities against KB-oral, MCF-7 and NCI-H187 cell lines with the IC 50 values of 18.01, 28.83 and 18.42 μg/mL, respectively. Friedelin, the mixture of α-amyrin and β-amyrin, lupeol and β-sitosterol were isolated from the active dichloromethane extract of the stems. Friedelin, the mixture of α-amyrin and β-amyrin, lupeol and β-sitosterol showed the antibacterial activity against E. coli with the MIC values of 250, 250, 250 and 1000 μg/mL, respectively. They also showed antibacterial activity against S. aureus with the MIC values of 250, 250, 500 and 1000 μg/mL, respectively. The mixture of α-amyrin and β-amyrin exhibited anticancer activity against MCF-7 cell line with the IC 50 value 28.45 μg/mL and lupeol exhibited anticancer activities against KB, MCF-7 and NCI-H187 cell lines with the IC 50 values of 30.12, 34.25 and 21.56 μg/mL, respectively. All the extracts and the isolated compounds were non-cytotoxic to Vero cells.